The Joint Effect of Bilingualism and ADHD on Executive Functions. (June 2015) - Mor, Billy; Yitzhaki-Amsalem, Sarin; Prior, Anat
Objective: The current study investigated the combined effect of ADHD, previously associated with executive function (EF) deficits, and of bilingualism, previously associated with EF enhancement, on EF.Method: Eighty University students, Hebrew monolinguals and Russian Hebrew bilinguals, with and without ADHD participated. Inhibition tasks were a Numeric Stroop task and a Simon arrows task. Shifting tasks were the Trail Making Test (TMT) and a task-switching paradigm.Results: Participants with ADHD performed worse than controls, but we did not find a bilingual advantage in EF. The negative impact of ADHD was more pronounced for bilinguals than for monolinguals, but only in interference suppression tasks. Bilingual participants with ADHD had the lowest performance.Conclusion: Bilingualism might prove to be an added burden for adults with ADHD, leading to reduced EF abilities. Alternatively, the current findings might be ascribed to over- or under-diagnosis of ADHD due to cultural differences between groups. These issues should be pursued in future research.